Optimization of Design Coordination Processes for a 7-Story Multifamily Building Using Virtual Design and Construction (VDC) - Fernández Bustamante, Diego Alfredo (2024)
Traditional construction and property companies often find themselves bound by conventional project management and design techniques, which can lead to delays during the design phase. This situation needs to be avoided. This study presents a process optimization for the design stage of multifamily buildings using Virtual Design Construction (VDC) - a collaborative project management approach. Focused on a case study involving two residential buildings developed by the same property company in Lima, Peru, this research commences with a comprehensive analysis of the existing design processes from the projects. By pinpointing key sources of variability and streamlining the design flow, the proposed VDC implementation aims to enhance compliance with project timelines and the approval of design drawings. The optimized process yielded tangible results, significantly reducing design time, completing tasks ahead of the scheduled deadline, and improving the delivery of technical files by 25%. These outcomes underscore the benefits of this optimized process, including enhanced project efficiency and improved design quality, thereby making a compelling case for applying VDC in similar construction projects by property companies.